Vaginal compared with intramuscular progestogen for preventing preterm birth in high‐risk pregnant women (VICTORIA study): a multicentre, open‐label randomised trial and meta‐analysis. (14th July 2020) - Choi, S‐J; Kwak, DW; Kil, K; Kim, S‐C; Kwon, J‐Y; Kim, YH; Na, S; Bae, J‐G; Cha, H‐H; Shim, J‐Y; Oh, KY; Lee, KA; et al.
Abstract : Objective: To compare the efficacy of two types of progestogen therapy for preventing preterm birth (PTB) and to review the relevant literature. Design: A multicentre, randomised, open‐label, equivalence trial and a meta‐analysis. Setting: Tertiary referral hospitals in South Korea. Population: Pregnant women with a history of spontaneous PTB or short cervical length (<25 mm). Methods: Eligible women were screened and randomised at 16‒22 weeks of gestation to receive either 200 mg of vaginal micronised progesterone daily (vaginal group) or an intramuscular injection of 250 mg 17α‐hydroxyprogesterone caproate weekly (IM group). Stratified randomisation was carried out according to participating centres and indications for progestogen therapy. This trial was registered at ClinicalTrials.gov (NCT02304237). Main outcome measure: Preterm birth (PTB) before 37 weeks of gestation. Results: A total of 266 women were randomly assigned and a total of 247 women (119 and 128 women in the vaginal and IM groups, respectively) were available for the intention‐to‐treat analysis. Risks of PTB before 37 weeks of gestation did not significantly differ between the two groups (22.7 versus 25.8%, P = 0.571). The difference in PTB risk between the two groups was 3.1% (95% CI −7.6 to 13.8%), which was within the equivalence margin of 15%. The meta‐analysis results showed no significant differences in the risk of PTB between the vaginal and IM progestogen treatments. Conclusion: Compared with vaginal progesterone, treatment with intramuscular progestin might increase the risk of PTB before 37 weeks of gestation by as much as 13.8%, or reduce the risk by as much as 7.6%, in women with a history of spontaneous PTB or with short cervical length. Tweetable abstract: Vaginal and intramuscular progestogen showed equivalent efficacy for preventing preterm birth before 37 weeks of gestation. Tweetable abstract: Vaginal and intramuscular progestogen showed equivalent efficacy for preventing preterm birth before 37 weeks of gestation.